Impact of Financial Literacy and Investment Understanding on Personal Financial Planning of IAIN Palopo Students - Abit, Muh.; Bachri, Samsul; Wahida, Altri (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
A person often has difficulty achieving financial stability due to financial problems, especially due to improper financial planning. This study aims to understand how financial literacy and investment understanding affect the personal financial planning of Palopo State Islamic Institute students. This study uses quantitative research methods. From the results of the t test analysis, it shows that financial literacy has a positive and significant impact on students' personal financial planning. Investment understanding has a positive and significant impact on students' personal financial planning. The F test results show that if students have financial and investment knowledge simultaneously, they have a positive and significant impact on their own financial planning